James R. Rush(2016). Hamka’s great story: A master writer’s vision of Islam for modern Indonesia. Madison, WI: University of Wisconsin Press, 286 pp. - Lundry, Christopher Alan (Estudios de Asia y África, 2018)
James R. Rush(2016). Hamka’s great story: A master writer’s vision of Islam for modern Indonesia. Madison, WI: University of Wisconsin Press, 286 pp.